ANALISIS GEOTEKNIK TERHADAP KERUSAKAN DAN PENINGKATAN JALAN KOLONEL IMAM SUPARTO KECAMATAN TEMBALANG STA. 4+700 - Okky Suya Sakti Saputra; Winner Bino Septino Sinaga; Indrastono Dwi Atmanto; Rudi Yuniarto Adi (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Kolonel Imam Suparto street has an important role for the economic growth in Subdistric of Tembalang. Recently, this road has catastrophic landslide. It is quite alarming. Degradation of this road as an impact of landslide is very danger for the safety of driver who pass through this way. After slope stability analysis using Fellenius method is performed, it is shown that the SF or safety factor of the slope is 0,891. By using PLAXIS 8.2 , it is shown that the SF is 1,37. Both of this point indicated that the slope stability is in a critical condition or very risk for landslide. So, a precise solution is needed to push the landslide risk by increased the safety factor of that slope. The alternatives that used for this case by using Retaining Wall (DPT) type Cantilever Wall and Bronjong DPT or Bronjong is quite good for solving the landslide. It is founded that after reparation by using DPT type cantilever wall the safety factor is 1,93 and 1,77 by using Bronjong. DPT type cantilever wall is decided as the best solution between both alternatives. It is because the safety factor of DPT is higher than Bronjong.